2013
DOI: 10.1128/jvi.00557-13
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Victorivirus from a Phytopathogenic Fungus, Rosellinia necatrix, Is Infectious as Particles and Targeted by RNA Silencing

Abstract: Japan bA novel victorivirus, termed Rosellinia necatrix victorivirus 1 (RnVV1), was isolated from a plant pathogenic ascomycete, white root rot fungus Rosellinia necatrix, coinfected with a partitivirus. The virus was molecularly and biologically characterized using the natural and experimental hosts (chestnut blight fungus, Cryphonectria parasitica). RnVV1 was shown to have typical molecular victorivirus attributes, including a monopartite double-stranded RNA genome with two open reading frames (ORFs) encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 77 publications
3
81
0
2
Order By: Relevance
“…7. approach. For example, several mycoviruses, including a hypovirus (CHV1), a mycoreovirus (MyRV1), a partitivirus (RnPV2), and a victorivirus (RnVV1), more effectively replicated in an RNA silencing-defective, dicer-like protein 2 knockout mutant strain of C. parasitica (⌬dcl-2) than in the wild-type strain of the fungus (11,33,34). Notably, both dcl-2 and agl-2 are upregulated by infection with CHV1 and MyRV1 and also by constitutive expression of dsRNA in C. parasitica (31,32).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…7. approach. For example, several mycoviruses, including a hypovirus (CHV1), a mycoreovirus (MyRV1), a partitivirus (RnPV2), and a victorivirus (RnVV1), more effectively replicated in an RNA silencing-defective, dicer-like protein 2 knockout mutant strain of C. parasitica (⌬dcl-2) than in the wild-type strain of the fungus (11,33,34). Notably, both dcl-2 and agl-2 are upregulated by infection with CHV1 and MyRV1 and also by constitutive expression of dsRNA in C. parasitica (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…6Q). It has been predicted that sense-strandspecific inverted repeat and panhandle structures exist between the 5= and 3= termini of genome segments of RnQV1, RnVV1, and RnMyRV3 (29,34,40,61); therefore, these secondary structures might be diced. In contrast, we found that vsRNA peaks were densely distributed at the 5= region of both RnPV1-S1 and RnPV1-S2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations